Aberrant cytokine expression in COVID-19 patients: Associations between cytokines and disease severity. (July 2021) - Tang, Yueting; Sun, Jiayu; Pan, Huaqin; Yao, Fen; Yuan, Yumeng; Zeng, Mi; Ye, Guangming; Yang, Gui; Zheng, Bokun; Fan, Junli; Pan, Yunbao; Zhao, Ziwu; et al.
Highlight: IL-6 and IL-10 play a crucial role in the pathogenesis of COVID-19. IL-6 and IL-10 are strictly related to the patients' OS and EFS. Combining IL-6 and IL-10 provide valuable information in predicting prognosis. Dynamic monitoring IL-6 and IL-10 offer the new ideas for COVID-19 therapy. Abstract: Cytokines play pleiotropic, antagonistic, and collaborative in viral disease. The high morbidity and mortality of coronavirus disease 2019 (COVID-19) make it a significant threat to global public health. Elucidating its pathogenesis is essential to finding effective therapy. A retrospective study was conducted on 71 patients hospitalized with COVID-19. Data on cytokines, T lymphocytes, and other clinical and laboratory characteristics were collected from patients with variable disease severity. The effects of cytokines on the overall survival (OS) and event-free survival (EFS) of patients were analyzed. The critically severe and severe patients had higher infection indexes and significant multiple organ function abnormalities than the mild patients ( P  < 0.05). IL-6 and IL-10 were significantly higher in the critically severe patients than in the severe and mild patients ( P  < 0.05). IL-6 and IL-10 were closely associated with white blood cells, neutrophils, T lymphocyte subsets, D-D dimer, blood urea nitrogen, complement C1q, procalcitonin C-reactive protein. Moreover, the IL-6 and IL-10 levels were closely correlated to dyspnea and dizziness ( P  < 0.05). The patients with higher IL-10 levels had shorter OS than the group with lower levels ( P  < 0.05). The older patients with higher levels of single IL-6 or IL-10 tended to have shorter EFS ( P  < 0.05), while the patients who had more elevated IL-6 and IL-10 had shorter OS ( P  < 0.05). The Cox proportional hazard model revealed that IL-6 was the independent factor affecting EFS. IL-6 and IL-10 play crucial roles in COVID-19 prognosis.